Do Muslim directors influence firm performance? empirical evidence from Malaysia - Haron, Razali (IIUM Press, International Islamic University Malaysia, 2018)
This study examines the impact of several corporate governance mechanisms on the performance of firms in Malaysia. Giving particular attention on board diversity, this study looks into the impact of Muslim directors in the board of directors (BoD) on firm performance. It is found that the presence of Muslim directors in the BoD does have a significant impact on the performance of the firms and can bring the firm to its utmost performance. Board independence seems to coexist with CEO duality in pursuing maximum firm value and directors’ remuneration does not seem to be the driver and motivator to achieve good firm performance. Board size is also taken into consideration when devising corporate governance structure where the larger the size of the board the better performance it is for the firms. Policy makers and other responsible players should take into account the mechanisms discussed in this study when structuring corporate governance. This study fills the gap and contributes significantly to the literature by proving extensive findings with regards to the impact of corporate governance on firms’ performance especially the presence of Muslim directors in BoD in Malaysia.